Perspektif Orangtua Terkait Kemandirian Anak Autis Pada Aspek Sosial - Ferasinta, Ferasinta (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2020)
Autism in children has several symptoms such as being unable to socialize, having difficulty using language, behaving repeatedly and reacting abnormally to stimuli. The purpose of this study was to describe the perspective of parents regarding the autonomy of children with autism in the social aspects of Soeprapto mental hospital, Bengkulu. This study used a qualitative descriptive method with a research sample of 10 informants and 4 autistic therapists. Data were obtained from interviews and observations. The results of the study obtained information from the social aspect of the child that they are willing to play with their peers and interact with the surrounding environment, are afraid of meeting people they do not know, ask to be welcomed when they meet close people such as father, mother and caregiver, but still many children who take autism therapy have not achieved a significant level of independence. This is due to the level of obedience of children with autism in following therapy or learning provided by therapists and support from children's families who only rely on the education provided by the therapist. In conclusion, the autonomy of children with autism has not reached a significant level of independence based on the parents' perspective. It is hoped that the results of this study can be input for educational institutions and related parties (therapists) as information and knowledge about the autonomy of children with autism from a social aspect.Â Keywords: Autistic Children, Social Independence, Parents' Perspective